MELATIH KETERAMPILAN PROSES SAINS SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN POE (PREDICTION, OBSERVATION, EXPLANATION) - Sinulingga, Pendi; Jhoni Hartanto, Theo; Adwitya, Winda (Vidya Karya Jurnal Kependidikan, 2015)
Based on the observation in the physical science instruction, especially in the material of harmonic vibration at SMAN 1 (Public Senior High School), Palangkaraya Municipality, it has been found that the instruction is only focused on the knowledge aspect of harmonic motion, but not yet focused on how to train the studentsâ KPS (Science Process Skills). One of the solutions being able to train the KPS is the instructionÂ model of POE (Prediction, Observaation, Explanation). The goal of this research is to train the mastery of the studentsâ science process skills and to know the result of the studentsâ cognitive learning after they have followed the instruction by implementing the POE model in the material of harmonious vibration. This research is a pre-experimental research. The research has been implemented in the 11th class of MIA 1 SMAN 1, Palangkaraya. Based on the research, it has been known that: (1) 20% of the students having the mastery of KPS with very good category, 55% of the students having the mastery of KPS with good category, and the remaining 25% of the studentsâ having the mastery of KPS with sufficiently good category, and (2) the completeness of the cognitive learning result showing the completeness of 36 students and the non-completeness of 4 students or 90% of the students in the 11th class of MIA 1 SMAN 1 Palangkaraya have reached the completeness.